2008
DOI: 10.1016/j.bbadis.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Antimycin A and lipopolysaccharide cause the leakage of superoxide radicals from rat liver mitochondria

Abstract: Here we show that both Antimycin A, a respiratory chain inhibitor inducing apoptosis, and endotoxic shock, a syndrome accompanied by both necrosis and apoptosis, cause not only an increase but also the leakage of superoxide radicals (O(2)(*-)) from rat heart mitochondria (RHM), while O(2)(*-) generated in intact RHM do not escape from mitochondria. This was shown by a set of O(2)(*-)-sensitive spin probes with varying hydrophobicity. The levels of O(2)(*-) detected in intact RHM gradually increase as the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…Therefore, we tested the effect of ROCK1 on mtROS production in the glomeruli of control and STZ-induced diabetic mice. To specifically assess mitochondrial superoxide production, we performed Electron Paramagnetic Resonance (EPR) spectroscopy, and used 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethyl-pyrrolidine (CMH) as the spin trap (Piskernik et al, 2008; Pospisilik et al, 2007). We observed ~ 8-fold increase in the mtROS generation from the isolated kidney glomeruli of diabetic wild type mice, whereas this increase was prevented in diabetic ROCK1 −/− mice (Figure 4A, left panel ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tested the effect of ROCK1 on mtROS production in the glomeruli of control and STZ-induced diabetic mice. To specifically assess mitochondrial superoxide production, we performed Electron Paramagnetic Resonance (EPR) spectroscopy, and used 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethyl-pyrrolidine (CMH) as the spin trap (Piskernik et al, 2008; Pospisilik et al, 2007). We observed ~ 8-fold increase in the mtROS generation from the isolated kidney glomeruli of diabetic wild type mice, whereas this increase was prevented in diabetic ROCK1 −/− mice (Figure 4A, left panel ).…”
Section: Resultsmentioning
confidence: 99%
“…It revealed that O 2 À is generated only in mitochondria that have experienced a shock, but not in intact ones. 90 Considering that PUFAs are particularly oxygen-sensitive compounds, it is hypothesized that peroxidation of PUFAs is the initiating process of all biological oxidation reactions. Usually it was assumed so far that LPO reactions are initiated by superoxide and not by the reaction of lipid hydroperoxides produced by cell injury as outlined above.…”
Section: Spitellermentioning
confidence: 99%
“…Reactive oxygen and nitrogen species in tissues were determined by electron paramagnetic resonance (EPR) spectroscopy using the membrane-permeable spin probe 1-hydroxy-3-carboxy-2,2,5,5-tetramethyl-pyrrolidine hydrochloride (CPH). In an endotoxic shock model, we recently found increased RONS generation and oxidative or nitrosylative stress in the liver using CPH (1). Reactive oxygen and nitrogen species scavenging capacity was analyzed by investigating protein levels of superoxide dismutase 2 (SOD-2), an antioxidative defense enzyme, induced after conditions associated with increased oxidative stress, such as hepatic I/R (2) and endotoxic shock (3).…”
Section: Introductionmentioning
confidence: 99%